LAW ENFORCEMENT AGAINST PERSONS OF CRIMINAL ACTIONS FOR FORGISTRATION OF DIPLOMAS IN LEGISLATIVE GENERAL ELECTIONS - Nurbaiti Syarif; Winda Yunita; Andri Putra Sela (PRANATA HUKUM, 2026)
The crime of forgery is regulated in Article 263, 264 of the Criminal Code in conjunction with Article 69 Paragraph (1) of Law Number 20 of 2003 concerning the National Education System. The crime of forgery of diplomas is an unlawful act that must be handled seriously in accordance with the rules and the role of the police and also law enforcers in order to maintain order and security for the community for the sake of upholding the law. The problem in this research concerns law enforcement against perpetrators of the crime of forgery of diplomas in legislative elections, the research method used is normative legal research and empirical legal research. Law enforcement against the crime of diploma forgery in the implementation of legislative elections is carried out using penal means. The penal approach is carried out by means of legal efforts, namely the perpetrators of the crime of diploma forgery are processed legally based on the provisions of Articles 263, 264 of the Criminal Code in conjunction with Article 69 Paragraph (1) of Law Number 20 of 2003 concerning the National Education System. It is hoped that the application of criminal sanctions in the use of fake diplomas will be optimized so that they can provide a deterrent effect and law enforcers must conduct more outreach to the public regarding the dangers of the crime of diploma forgery.